Supporting womens groups and networks- visibility, voice and influence in market systems and agriculture sector governance - Mepham, Inga (TOMAK, 2019)
Presented by Inga Mepham (TOMAK), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.